Impact of rooftop PV generation on distribution transformer and voltage profile of residential and commercial networks - Masoum, A.; Moses, P.; Masoum, Mohammad Sherkat; Abu-Siada, Ahmed (Institute of Electrical and Electronics Engineers, 2012)
Integration of rooftop PVs in residential networks at moderate penetration levels is becoming a reality in many countries including Australia. However, the detrimental effects associated with the high penetrations levels of rooftop PVs are not fully explored to most power utilities. It is expected that the sophisticated structure and communication backbone of smart grid allow easy, safe and reliable integration of these distributed renewable energy resources at very high penetration levels in the residential networks populated with smart appliances. However, it could take several years before smart grid infrastructure is ready to support high perpetrations of distributed generations. Therefore, until smart grid communication becomes available, utilities need to explore how present-day residential networks will cope with the fast installations of rooftop PV systems. In particular, the burden on local distribution circuits such as transformers and cables, which are the critical links in distribution systems, must be investigated in the presence of PVs. This paper carries out an analysis into the impacts of rooftop PVs at different penetration levels on the performance of distribution transformers and residential networks. Such operation may lead to an overall reduction in the reliability and economy of future smart grids. Simulation results are presented to demonstrate voltage profiles and distribution transformer stresses for a realistic 97 node residential network at various penetrations of rooftop PVs.